The Role of Collaboration in Innovation and Value Creation in the Aviation Industry. (May 2021) - Pereira, Bruno; Lohmann, Gui; Houghton, Luke
Collaboration plays a critical role in fostering innovation and value creation in the aviation sector. However, how factors and connections relate to the achievement of innovative outcomes in aviation require further investigation. This study investigates the key factors that create a conceptual framework by conducting a literature review and an archival analysis of news articles. The model proposed involves factors such as strategic decision-making; networking and partner choice; cultural context, values, behaviour and compatibilities; collaboration configuration; issues and risks shared; skills, capacities and experience; infrastructure and resources available; engagement activities; knowledge transfer, absorption and appropriation; collaboration management; communication flows; external environment and demand; and expectations and outcomes. Promising collaborations are also indicated in areas where the framework could be adopted to increase partnerships and outcomes. Also, we highlight best practice examples from leading organizations, such as International Airlines Group (IAG), Emirates Airline, Singapore Airlines, Boeing and JetBlue, to provide insights into existing collaborations that have led to innovation and value creation in this sector.